Memo from James C. Sternberg to T. E. Kristofferson - Sternberg, James C. (1965)
Dr. Sternberg does not believe that Perkin-Elmer, Inc. can patent a flame ionization detector, as their instrument would be too similar to the one described in this German patent. The Perkin-Elmer instrument would be in direct competition with a flame ionization detector manufactured by Beckman Instruments, Sternberg's employer.
Keywords: Perkin-Elmer Corporation; Scientific apparatus and instruments; Patents; Gas chromatography--Instruments; Beckman Instruments, Inc.